EDUCATIONAL TRANSFORMATIONS IN SOCIAL MEDIA: IMPLICATIONS FOR TEACHING AND RESEARCH IN HIGHER EDUCATION - Alves Gadelha Trigueiro, Valdiza; Clécia Santana de Sousa, Ana; Antonio Cartaxo, Carlos; Alves de Freitas, Edriana; Carlos Vieira, Espedita; Alves Gonçalves, Erivan; Batista Alves, Inês; Pamplona Pinheiro, Soliesandro; Clementino Dantas, Temístocles; de Sousa, Vivianne (Revista Gênero e Interdisciplinaridade, 2025)
This paper explores the educational transformations brought about by social networks and their implications for teaching and research in higher education. Based on a critical analysis of the interaction between students and teachers on social platforms, the study seeks to understand how these digital tools influence learning, collaboration and knowledge construction processes. In addition, the study investigates the challenges and opportunities that arise with the use of social networks in the academic environment, proposing strategies to integrate them in a meaningful way into the curriculum. The objective is to provide a reflection on the evolution of higher education in a connected world, highlighting the importance of social networks as agents of educational change.